Bandgap Engineering and Near-Infrared-II Optical Properties of Monolayer MoS2: A First-Principle Study - Yang, Ke; Liu, Tianyu; Zhang, Xiao-Dong (Frontiers in Chemistry, 2021)
The fluorescence-based optical imaging in the second Near-Infrared region (NIR-II, 1000-1700 nm) has broad applications in the biomedical field, but it is still difficult to find new NIR-II fluorescence materials in the two dimensional. As a crucial characteristic of the electronic structure, the band structure determines the fundamental properties of two-dimensional materials, such as their optical excitations, electronic transportation, etc. Therefore, we calculated the electronic structures and optical properties of different crystalline phases (1T phase and 2H phase) of pure monolayer MoS2 films and found that the 1T-phase has better absorption and thus better fluorescence in the NIR-II window. However, its poor stability makes the 1T-phase MoS2 less useful in the vivo bioimaging. Via introducing vacancy defects and doping with foreign atoms, we successfully tuned the band gap of the monolayer 2H-MoS2 and make it activated in the NIR-II. Our results show that, by engineering the vacancy defects, the band gap of the 2H phase can be tailored to around 1 eV, and there are three candidates of vacancy structures that exhibit strong absorption in the NIR-II.